Discovery of ammonoid jaw apparatus and associated features using reflectance transformation imaging (RTI) - Moron Alfonso, Daniel Andres (2023)
We report on remains of the buccal apparatus and possible associated structures for the Late Cretaceous ammonite Maorites seymourianus from the Lopez de Bertodano Formation (Antarctic Peninsula). This is the first description of these structures for the family Kossmaticeratidae. Further, we discuss the most likely taphonomic processes taking place that allowed this exceptional preservation. Reflectance Transformation Imaging (RTI) technique was employed in this work to better document the faint structures. We briefly provide a review of this method and its potential importance for paleontological studies because it seems that this powerful technique has been largely overlooked by paleontologists.